Peran Orang Tua Dalam Mendukung Pembelajaran Matematika di Rumah Bagi Siswa Sekolah Dasar - Hardika Saputra (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study aims to understand the critical role of parents in supporting children's mathematics learning at the elementary school level. In this context, the research employs a qualitative approach with a case study design to explore parental involvement in facilitating mathematics comprehension at home and collaboration with teachers. Data were collected through in-depth interviews, participatory observations, and document analysis of ten purposively selected families. The results indicate that effective communication between parents and teachers, as well as the support provided at home, plays a significant role in enhancing children's understanding and motivation in learning mathematics. Parents who are actively involved in their children's learning, both through direct interaction with teachers and by facilitating learning activities at home, are proven to help children overcome challenges in learning mathematics. The study also emphasizes the importance of consistent collaboration between home and school to create a supportive learning environment. The implications of this study suggest that active parental involvement and collaboration with teachers are crucial for achieving optimal mathematics learning outcomes.